Genomic Selection Module 2.0b—What is genomic selection? - International Livestock Research Institute (International Livestock Research Institute, 2017)
Part 2b in a series of eight training modules on Genomic Selection. The modules are prepared by the Clay Sneller, lead plant breeder at the Biosciences eastern and central Africa-International Livestock Research Institute (BecA-ILRI Hub), in Nairobi